Explaining Financial Management Behavior among Millennials: The Influence of Fintech Adoption, Financial Literacy, and Social Factors - Supriyono, Edi; Wiranda, Zahra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid development of digital financial services has transformed the way individuals manage their personal finances, particularly among millennials who are highly exposed to technological innovations. Despite the increasing availability of financial technology (fintech), many individuals still experience difficulties in managing their financial resources effectively. This study aims to examine the influence of financial technology, financial literacy, financial attitude, financial confidence, and peer influence on financial management behavior among millennial. A quantitative research approach was employed using primary data collected through an online questionnaire. A total of 240 millennial household heads were selected using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 4.0. The results show that financial technology and peer influence have a positive and significant effect on financial management behavior, while financial confidence has a negative and significant effect. Meanwhile, financial literacy and financial attitude do not have significant effects on financial management behavior. These findings suggest that technological accessibility and social interactions play a more prominent role in shaping financial behavior than financial knowledge and attitudes alone. This study contributes to the financial behavior literature by highlighting the importance of technological and social factors in influencing household financial management among millennials in emerging economies.